From the mountains to the sea : protecting nature in postwar New Hampshire - Jarvis, Kimberly A. (Environmental history of the Northeast., 2020)
"In the face of increasing pressures from business and government in the decades following World War II, New Hampshire residents banded together to preserve their most prized natural areas and defining geological features. From the Mountains to the Sea explores how history, memory, and tradition created a strong sense of place in the state that led citizen activists to protect Franconia Notch, Sandwich Notch, and the town of Durham on New Hampshire's seacoast from development in the last half of the twentieth century. These efforts led to the construction of a parkway instead of an interstate highway, prevented the building of an oil refinery, and saved Sandwich Notch from becoming a vacation community. Shaped by New Hampshire's unique conservation focus on both resource use and preservation that developed during the first years of the twentieth century, as well as on the tradition of home rule in the state, the outcome of each campaign relied on the insight into, appreciation for, and dedication to protecting the historic and aesthetic values of these three places"